If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -6(4v + -1) = v + 15 Reorder the terms: 9 + -6(-1 + 4v) = v + 15 9 + (-1 * -6 + 4v * -6) = v + 15 9 + (6 + -24v) = v + 15 Combine like terms: 9 + 6 = 15 15 + -24v = v + 15 Reorder the terms: 15 + -24v = 15 + v Add '-15' to each side of the equation. 15 + -15 + -24v = 15 + -15 + v Combine like terms: 15 + -15 = 0 0 + -24v = 15 + -15 + v -24v = 15 + -15 + v Combine like terms: 15 + -15 = 0 -24v = 0 + v -24v = v Solving -24v = v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1v' to each side of the equation. -24v + -1v = v + -1v Combine like terms: -24v + -1v = -25v -25v = v + -1v Combine like terms: v + -1v = 0 -25v = 0 Divide each side by '-25'. v = 0 Simplifying v = 0
| 8x-3.8=-8x-7.0 | | 5x-18-4x=-36 | | 6x-1.1=-5x+6.6 | | 5x+2(1-x)=2(2x-1) | | -10n+7=-3 | | 7x-2.7=-6x-7.9 | | 7x-1.2=3x-4.8 | | k(11-k)+(12-k+1)=(k+1)(11-k+1) | | 7x-0.96=6(x-0.67) | | 5x+2.9=6x+2.8 | | -6x+3.2=-3x+4.4 | | 5x+1.2=x+3.6 | | 5x-0.1=3x | | -2(x-1)=14 | | 16X^2=25 | | -7(5-4x)=189 | | 3x+0.6=x | | 35=5 | | 2x^2+1x-3=0 | | 35=-5 | | 4(x-6)=-52 | | 2(x+2)=-14 | | 3(x+9)=45 | | 2(x+2)=-8 | | 81x^2=25 | | 5(x-3)=-50 | | 3(x-8)=-45 | | 9x^2=16 | | 5(x+5)=40 | | 25x^2=36 | | 3(x-9)=-24 | | 5(x+7)=50 |